(untitled) (UNIZIK Journal of STM Education, 2025)
Driving technological competitiveness through curriculum innovation is essential for preparing students to thrive in the modern world. It enhances digital literacy, critical thinking, and student engagement, aligning education with the demands of the 21st century. Recognizing this, this study investigated the driving technological competitiveness through curriculum innovation in Biology education: a position for 21st century learning reforms. Three research questions guided the study. The study adopted a descriptive survey design. The entire population of 48 Biology teachers from Aguata LGA in Anambra State was used hence no sampling. Data collection involved a 30 structured questionnaire items, validated by three experts. The instrument demonstrated high reliability, with a Cronbach’s alpha of 0.85. The analysis employed the mean score and standard deviation to identify general consensus among respondents. Findings revealed that teachers face significant challenges in integrating technology into Biology curricula, including limited access to technological resources, inadequate training, and resistance to change. Despite these obstacles, teachers strongly agreed that technology-enhanced curriculum positively impact and prepare learners for the global workforce. The study also revealed the potentials of technology to make Biology lessons more engaging and interactive. Respondents favored strategies such as regular professional development focused on digital literacy, increased infrastructural support, and curriculum reforms that embed digital competencies. The study recommends continuous updates to the Biology curriculum to embed emerging technologies and digital tools, making it more relevant and engaging for students. The study concluded that curriculum innovation is crucial for bridging the gap between traditional teaching methods and modern learner needs.